PENGARUH LIKUIDITAS , LEVERAGE, DAN PROFITABILITAS TERHADAP KEBIJAKAN DEVIDEN - Lonardo, Felix; Tjakrawala, Kurniawan (Jurnal Paradigma Akuntansi, 2025)
This research aims to test empirically the effect of liquidity, leverage, and profitability to dividend policy in manufacturing companies listed on the Indonesia Stock Exchange from 2018 to 2021. This study used 20 data from consumer goods industries that have been selected using purposive sampling method. The data used are secondary data in the form of financial statements. Research data processing uses the program SPSS 21. The result of research shows that liquidity has a positive effect on dividend policy, leverage has a negative effect on dividend policy, profitability has a positive effect on dividend policy.